2020
DOI: 10.1186/s12891-020-03513-w
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral patellar tendon rupture on lupus undergoing corticosteroids: a case report

Abstract: Background: Patellar tendon rupture is a rare condition, especially when it is bilateral. The most frequent associated pathologies are systemic lupus erythematosus, chronic renal failure, or treatments like corticosteroids. The aim of this case report is to draw attention to the non-specific clinical aspect of this condition, to recall its radiological signs, and highlight the diagnostic contribution of musculoskeletal ultrasound. Case presentation: A 39-year-old man was diagnosed with a systemic lupus erythem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Early tendon repair can prevent proximal patella tendon retraction, scarring, and diminished long-term function [ 16 ]. Primary tendon repair is commonly performed via suture repair on a healthy tendon with some authors advocating the use of wire cerclage on degraded tendons [ 14 , 17 ]. Postoperative rehabilitation and therapy is generally recommended, but there is no current consensus or standard therapy regimes [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Early tendon repair can prevent proximal patella tendon retraction, scarring, and diminished long-term function [ 16 ]. Primary tendon repair is commonly performed via suture repair on a healthy tendon with some authors advocating the use of wire cerclage on degraded tendons [ 14 , 17 ]. Postoperative rehabilitation and therapy is generally recommended, but there is no current consensus or standard therapy regimes [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…One patient had both MRI and ultrasonography as secondary investigations. Only eight cases [2,24,[36][37][38][39][40][41] reported the Insall-Salvati ratio found during imaging. Of those presented, we found a mean Insall-Salvati ratio of 1.62 for the right patella and 1.60 for the left patella, which confirmed that patella alta is a high-yield finding in the diagnosis of patellar tendon rupture.…”
Section: Diagnostic Processmentioning
confidence: 99%
“…The big majority of the cases reported were treated with direct primary repair (40 patients), and over half of these cases required augmentation of some type, i.e., tendons, cerclage wires or tension band wiring [1][2][3]11,12,24,28,37,39,40,41,[46][47][48][49][50][51][52][53][54]. The most commonly used method for augmentation was using cerclage wires (12).…”
Section: Treatmentmentioning
confidence: 99%
“…Tendon rupture is a severe, albeit rare, manifestation of SLE. In a recently published case report, El Ouazi et al showed the value of US and MRI in the diagnosis of bilateral patellar tendon rupture in a patient with SLE [ 50 ]. Hosokawa et al highlighted the case and the imaging findings of a SLE patient with spontaneous rupture of the flexor tendon of the little finger [ 51 ].…”
Section: Sle Arthropathymentioning
confidence: 99%